2017
DOI: 10.1159/000458520
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of the Angiotensin II Type I Receptor (<b><i>AGTR1</i></b>) Gene Along with Environmental Factors Increases the Risk for Essential Hypertension

Abstract: Objectives: The present study aimed to evaluate the hypertension status of community residents, analyze environmental and epigenetic factors, and propose prevention measures for hypertension. Methods: In our study, different methylation levels were distinguished utilizing melting temperature (Tm) values in both the case and the control group. Multiple logistic regression analysis was used to estimate the risk of having essential hypertension (EH) between hypertensive and nonhypertensive participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
2
8
1
1
Order By: Relevance
“…Notably, smoking and drinking are also important risk factors for hypertension, and both interact with DNA methylation of genes to affect the risk of EH . However, we did not observe any significant interactions in our study, although future studies with larger sample size are needed to confirm our findings.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Notably, smoking and drinking are also important risk factors for hypertension, and both interact with DNA methylation of genes to affect the risk of EH . However, we did not observe any significant interactions in our study, although future studies with larger sample size are needed to confirm our findings.…”
Section: Discussioncontrasting
confidence: 45%
“…Increasing the methylation level of a promoter region will silence the transcription of the corresponding gene, whereas decreasing it may promote gene transcription . Aberrant gene methylation has been identified as an important contributor to the pathogenesis of EH, for example, hypomethylation of interleukin‐6 ( IL‐6 ), angiotensin II type 1 receptor ( AGTR1 ), angiotensin‐converting enzyme ( ACE ), Na+/K+/Cl− cotransporter protein 1 ( NKCC1 ), and α‐adducin ( ADD1 ), and the hypermethylation of 11β‐hydroxysteroid dehydrogenase type II ( 11β‐HSD‐2 ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that hypomethylation mechanisms can lead to higher ACE, β‐adrenergic receptors and Na + channel expression in the hypertensive condition . In agreement with this, it was recently demonstrated that the hypo‐methylation process of the angiotensin II type I receptor (AGTR1) and interleukin‐6 gene in peripheral blood DNA, increase the risk of essential hypertension in human.…”
Section: Epigenetic Modifications: a Potential Pathway Linking Maternmentioning
confidence: 59%
“…Lin et al reported that hypomethylation of the angiotensin II type I receptor gene correlated with higher systolic and diastolic BPs. Smokers with HTN were also observed to have a lower level of methylation ( 66 ).…”
Section: Epigenetics Of Htnmentioning
confidence: 99%